The Effect of Review Video Making on Problem Based Learning to Spatial Ability - Dewi Satria Ahmar; Muhammad Fath Azzajjad; Ansari Saleh Ahmar (PT Mattawang Mediatama Solution, 2022)
The aims of thi study is to know the effect of review video making on problem based learning to spatial ability. This research is a quasy experimental research using posttest only control design. The experimental class applied video review on problem-based learning model and the control class did not do video review but only applied problem-based learning model. The population in this study amounted to 49 people and the research sample was 40 people. The sampling technique used in determining the research sample was purposive sampling technique. The research instrument used an essay test which was prepared based on indicators of spatial ability consisting of spatial perception, mental rotation, and spatial visualization. Data analysis techniques include descriptive analysis and inferential analysis. Descriptive data analysis describes the comparison of spatial ability scores of experimental and control classes while inferential analysis is used to test the hypothesis. Descriptive analysis of spatial abilities obtained the average value of the experimental class and control class is 90.50 and 59.50, The results of the spatial ability analysis test using the Mann-Whitney test showed a significance value <0.05, indicating that there is an effect of reviewing student-made videos in the Problem Based Learning Integrated Project assignment learning model on spatial abilities.